Effects of Beta-Glucan on non-specific immune response in grouper (Epiniphelus coioides). - Tavarro, Rover John Gonzales
The use of immunostimulants in fish culture is an alternative approach to disease prevention and control. It enhances the non-specific defense thereby inducing generalized protection. The immunostimulatory effect of B-1,3 glucan in several fish species is well documented but its effect in grouper Epinephelus spp. requires further investigation., Curdlan, a B-1,3 glucan extracted from bacterium Alcaligenes faecalis, was injected intraperitoneally to groupers, Epinephelus coioides to determine its effect on the non-specific immune response. Hematocrit level, total and differential leukocyte counts, NBT reduction, lysozyme and bacterial activities were used to evaluate the effects of different doses (0.5, 5.0, 10, 20, and 50mg/kg body weight) of immunostimulant after seven days of treatment. A significant (p<0.05) increase in the total leukocyte count was noted in the treated fish. It was observed that the percentage of granulocytes and monocytes increased while the lymphocite numbers decreased in the differential leukocyte count in fish treated with curdlan. These changes in the leukocyte composition was significant (p<0.05) over the untreated fish. Hematocrit levels were not significantly affected by currdlan treatment. The production of superoxide anion, determined by NBT reduction, was significantly (p<0.05) higher in most treatments with curdlan. Treated fish were observed to have increased plasma lysozyme activity. However, a statistical difference was noted only in the 5mg/kg treatment. Similar results were obtained in the bacterial assay against Vibrio anguillarum. Groupers injected with curdlan at a dose of 5 mg/kg body weight exhibited the most significant (p<0.05) changes in the parameters tested. Results of the present study suggest that curdlan can enhance the non-specific defenses of grouper. This opens the possibility of using immunostimulants in grouper culture to enhance immunocompetency and disease resistance thereby minimizing mortalities and increasing its production.